HUMAN ENHANCEMENT AND SEXUAL DIMORPHISM - Sparrow, Rob (Bioethics, 2012)
I argue that the existence of sexual dimorphism poses a profound challenge to those philosophers who wish to deny the moral significance of the idea of ‘normal human capacities’ in debates about the ethics of human enhancement. The biological sex of a child will make a much greater difference to their life prospects than many of the genetic variations that the philosophical and bioethical literature has previously been concerned with. It seems, then, that bioethicists should have something to say about the choice between a male and a female embryo. Either, 1) parents have reason to choose boys over girls; (2) parents have reason to choose girls over boys; or, (3) parents have neither reason to choose girls over boys nor reason to choose boys over girls. Embracing either of the first two alternatives has strongly counterintuitive – and arguably morally repugnant – consequences. To motivate the third option we must either make reference to the idea of ‘normal human capacities’ or argue that parents should consider the interests of society when thinking about what sort of children they should bring into the world – an implication that should be extremely controversial in debates about the ‘new eugenics’. I conclude, then, that the idea of ‘normal human capacities’ is properly crucial to reasoning about the ethics of shaping future persons.